PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY ( TSTS ) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 019 SEKELADI ROKAN HILIR - Mislan, Mislan; Kurniaman, Otang; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstact: This study was conducted in SDN 019 Sekeladi which students acquire social studies results with an average low value. Therefore, the authors do a TOD with implementing cooperative learning model two stay two stray (TSTS). This study aims to determine the activities of teachers and students in learning activities using cooperative learning model two stay two stray (TSTS). To find out the results of social studies fourth grade students of SDN 019 Sekeladi. Data were collected through observation and data sheets Cooperative Learning Model Type two stay two stray (TSTS) through daily test cycles I and II for the daily test cycle learning outcomes data. Teacher activity at the first meeting of the first cycle is the percentage of all teachers be 75.0 66.66 at the second meeting. The first meeting on the second cycle to 83.33, the second meeting increased to 95.83. Activities of students in meeting the first cycle increment percentage is 58.33 student activity becomes 70.83. The first meeting on the second cycle increased to 79.16, the second meeting becomes 95.83. Improving student learning outcomes, on the basis of scores of students the average value is 45.83 in the first cycle increased 50.0 second cycle increased to be 87.5. increase in the percentage of students learning classical completeness on the basis of a score of 45.8 increased to 50.0 in the first cycle, the second cycle increased to 87.5. Based on the research and discussion that has been done can be concluded that the type of cooperative learning model two stay two stray (TSTS) can improve student learning outcomes in social studies.Key Words: Cooperative Type TSTS, Learning Outcomes